PENGARUH PENYULUHAN KESEHATAN DENGAN MEDIA AUDIO VISUAL TERHADAP PERILAKU MEROKOK PADA REMAJA DI SMPN 1 SAWOO - Devy Intan Kurniawati; Sulistyo Andarmoyo; Nurul Sri Wahyuni; Elmie Muftiana; Rika Maya Sari (Health Sciences Journal, 2022)
Smoking is one of the public health problems in Indonesia given that smoking is one of the main risk factors for several chronic diseases that can lead to death. This study aims to determine whether there is an effect of health education with audio-visual media on smoking behavior in adolescents. The design of this research is to use the Pre Experiment method with the One Group Pretest-Posttest Design. The population in this study were grade IX students at SMPN 1 Sawoo with a sample size of 40 respondents. In this study using purposive sampling. Data collection techniques using questionnaires and analysis using the Wilcoxon signed Rank Test. The results of this study indicate that there is an increase in good behavior about smoking. Statistical test results show the value of Asymp. Significant (2-tailed) 0.05, which means Ha is accepted, that is, there is an effect of health education with audio-visual media on smoking behavior in adolescents.